The Relationship Between Family Food Security and The Nutritional Status of Toddlers in Tamalate Sub-District, Makassar City - Isymiarni Syarif; Suriati Lubis; Ai Nurhayati; Muntasir; Nur Agustin Mardiana (Jurnal Penelitian Pendidikan IPA, 2024)
Food security is a condition where food is sufficiently available for one's body. The magnitude of the impact caused by the lack of food security makes it necessary to pay attention to its availability because this can cause problems of malnutrition so that health status decreases. The purpose of this study was to determine the relationship between family food security and the nutritional status of toddlers in Tamalate sub-district, Makassar City. The method used is observational using the design case-control with descriptive research design using quantitative and qualitative approaches. Data collection was carried out by means of observation, interviews with mothers who have children aged 23-60 months as many as 73 toddlers. The results showed that toddlers who experienced Normal Nutrition were as many as 24 toddlers with Food Resilience, followed by Light Food Insecurity 12 toddlers with Malnutrition status with a value of 0.05 P-Value = 0.045 < 0.05 and it can be concluded that there is a relationship between food security and the nutritional status of toddlers in the Tamalate Health Center environment which is located in Kel. Pr Tambung Kec. Tamalate Makassar City. This research can then be used as information material for further related research.